Residues of the British Informal Empire: the Smyrna-Aydın Railway's Punta Square as the Future Centre of "Colonial" Smyrna - Erten, Erdem; Sheridan Gun, I.T.; Erten, E. (Routledge, 2025)
Railways played a pivotal role in the Industrial Revolution, inspired by the expansion of colonial ambitions. They were often accompanied by infrastructural landmarks as postal offices, churches, and hospitals, representing imperial authority and connectivity. While the presence of these enclaves within colonies has been extensively studied, their significance in non-colonised regions, particularly within the Ottoman Empire, has received insufficient attention. The transformation of Smyrna (modern-day Izmir, Turkey) in the late nineteenth century reflects a reorganisation that aligned with Britain’s gentlemanly capitalism and imperialism. This paper aims to shed light on this subject through a detailed analysis of the Punta Railway Station and its surrounding area. Often relegated to a footnote in historical narratives as a “Little British Town,” the study area warrants re-evaluation in the context of informal imperialism. It illustrates how British colonial influence shaped Punta’s spatial and functional dynamics, embodying the concept of colonised spaces without formal colonisation. © 2025 Elsevier B.V., All rights reserved.
Residues of the British Informal Empire: The Smyrna–Aydın Railway’s Punta Square as the Future Centre of ‘Colonial’ Smyrna
Keywords: British Imperialism In Turkey; British Informal Empire; British Railways; Smyrna; İzmir